Functional Economies Or Administrative Units in Greece: What Difference Does It Make for Policy? - Prodromos-Ioannis Prodromidis (European Regional Science Association (ERSA), 2006)
The paper provides the 2001 income mosaic of Greece at the local (municipal and postcode) level, and econometrically isolates a number of territorial, demographic, and occupational factors on declared income formation, on the basis of which it makes a number of policy proposals. The disaggregate nature of the data facilitates the construction of alternative spatial models that are juxtaposed to the regional framework on the basis of which national and E.U. sub-national convergence and prosperity plans are devised, implemented, and assessed. A specification based on the existing regional framework provides an inferior econometric fit, which, in turn, suggests that the economy does not operate according to the country's administrative divisions but rather according to local-specific factors and transportation linkages, as is the case in a fragmented land united by its trans-portation network. Accordingly, if income disparities are larger within administrative regions rather than across regions, it might make more sense if regional economic development policy were con-ducted within a functional-area framework rather the current administrative-region framework. Suited for themes A, C, E, Q.
Keywords: 330